New Criterias of Synchronization for Discrete-Time Recurrent Neural Networks with Time-Varying Delay via Event-Triggered Control - Lei Yu; Guici Chen; Feng Jiang; Zhi Wang (Mathematics, 2022)
This paper mainly researches the synchronization issue of discrete-time recurrent neural networks (DTRNNs) with time-varying delay based on event-triggered control (ETC). ETC can effectively decrease the quantity of controller updates performed and the utilization of communication resources. By using Lyapunov–Krasovskii functional (LKF), Schur complement lemma, discrete time free weight matrix method, linear matrix inequalities (LMIs) and other analytical methods, the stability conditions of the error system are deduced. Accordingly, a class of event-triggered state feedback controllers is designed. Finally, through two numerical examples with simulations, the effectiveness of the controller is verified.